Kinematic Differences Between the Dominant and Nondominant Legs During a Single-Leg Drop Vertical Jump in Female Soccer Players. Issue 10 (August 2022) - Nakahira, Yu; Taketomi, Shuji; Kawaguchi, Kohei; Mizutani, Yuri; Hasegawa, Masato; Ito, Chie; Uchiyama, Emiko; Ikegami, Yosuke; Fujiwara, Sayaka; Yamamoto, Ko; Nakamura, Yoshihiko; Tanaka, Sakae; et al.
Background: In soccer, the roles of the dominant (kicking) and nondominant (supporting) legs are different. The kinematic differences between the actions of the dominant and nondominant legs in female soccer players are not clear. Purpose: To clarify the kinematic differences between dominant and nondominant legs during a single-leg drop vertical jump (DVJ) in female soccer players. Study Design: Controlled laboratory study. Methods: A total of 64 female high school and college soccer players were included in this study. Participants performed a single-leg DVJ test utilizing video motion capture with artificial intelligence during the preseason period. This study assessed the knee flexion angles, knee valgus angles, hip flexion angles, and lower leg anterior inclination angle at 3 time points (initial contact, maximum flexion of the knee, and toe-off) and compared them between the dominant and nondominant legs. These angles were calculated from motion capture data and analyzed in 3 dimensions. A paired t test was used to analyze the differences between legs, and the significance level was set at P < .05. Results: The knee valgus angle at initial contact was greater in the nondominant leg (mean ± SD, 0.8°± 5.2°) than the dominant leg (−0.9°± 4.9°) ( P < .01). There were no differences between legs for any other angles at any of the time points. Conclusion: The kinematics of the dominant and nondominant legs of female soccer players in a single-leg DVJ differ in knee valgus angle. Clinical Relevance: Leg dominance is associated with the risk of sports injuries. Kinematic differences between the dominant and nondominant legs may be a noteworthy factor in elucidating the mechanisms and risk of sports injury associated with leg dominance.